COMPARISON OF ENDOTHELIAL CELL CHANGES AFTER CATARACT SURGERY: PHACOEMULSIFICATION VERSUS MANUAL SMALL INCISION CATARACT SURGERY - Motwani, Jigna; Kher, Praveena (International Journal of Psychosocial Rehabilitation, 2020)
Cataract surgery has documented evidence of incurring loss of endothelial cells post-surgery. It is essential to assess the amount of endothelial cell loss after phacoemulsification which is the recently widely used and more preferable type of cataract surgery over small incision cataract surgery and to assess whether this procedure has minimum corneal endothelial cell loss ensuring better visual prognosis of the patient. ObjectivesTo compare the loss of endothelial cells and hexagonality of cells in phacoemulsification and small incision cataract surgery. To assess central corneal thickness pre and postoperatively. Methodology- This is a cross sectional study of 300 sample size where specular microscopy will be done before cataract surgery and on two followup visits. Data will be compiled and both surgical techniques: phacoemulsification and small incision cataract surgery will be compared with respect to endothelial cell loss and thickness of central cornea. ResultsThe expected outcome of the study would be the resultant cell affection of endothelial layer after phacoemulsification versus small incision cataract surgery suggesting more loss after phacoemulsification. Conclusion- Manual Small incision cataract surgery will prove to be a safer surgical technique in terms of corneal endothelial cell protection. Keywords- phacoemulsification, endothelial cell loss, small incision cataract surgery, Specular microscopy.